Removal of Heavy Metals from Synthesis Industrial Wastewater Using Local Isolated Candida Utilis and Aspergillus Niger as Bio-Filter - Ali, Safaa Abd Alrasool (The International Journal of Biotechnology, 2013)
In this study biomass filter of Candida Utilis which isolated from food sample in Baghdad local market and Aspergillus Niger which isolated from Baghdad soil used to biosorption heavy metals from synthesis industrial wastewater. two bio-filters were designed as cylindrical Perspex with height 10cm, diameter 3cm as a shell and inside their are layers of Sponge were prepare as the size of diameter of the cylindrical filter with thickness of 2cm arrange inside it, biomass production were 6 g of Aspergillus Niger and 5.6 g of Candida Utilis spreads between Sponges. pH, residence time, flow rate were tested as parameters, Optimum removal efficiency of Chromium, Lead, and Nickel were 89%, 90%, and 91% for Aspergillus Niger bio-filter, while it was 81%, 83%, 80% for Candida Utilis bio-filter at pH 6, residence time 10 min, flow rate 9 ml/min.